Do preoperative interventions affect patient satisfaction or expectation fulfilment following total hip arthroplasty? A systematic review - April-Rose Matt; Joanne L. Kemp; Andrea B. Mosler; Lucy Salmon; Diogo Almeida Gomes; Alysha De Livera; Erica Hateley; Adam L. Semciw (JSAMS Plus)
Background: Preoperative interventions are routinely implemented for patients undergoing total hip arthroplasty (THA), but little is known about how they affect patient satisfaction. With THA numbers projected to rapidly increase, the efficacy of perioperative models of care should be explored. This systematic review aimed to investigate the impact of preoperative interventions on patient satisfaction following THA. Methods: MEDLINE, EMBASE, Cochrane Register of Clinical Trials, CINAHL and Sports Discus were searched from inception to May 2023. Randomised and quasi-experimental trials of interventions before THA that reported outcomes on patient satisfaction or expectation fulfilment were included. Secondary outcomes analysed were pain, function, length of stay (LOS), and postoperative complications. Meta-analysis was performed, and the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach was used to rate the quality of the body of evidence. Results: Seven studies were included. Participants who received preoperative interventions were more satisfied (SMD -0.54 [-0.87, −0.21] p ​= ​0.001), and had better function postoperatively when compared to controls (SMD -1.86, 95%CI, −3.11, to 0.61, p ​= ​0.004). There was no difference between groups in pain outcomes (SMD -0.37, 95 ​% CI -0.86, 0.12, p ​= ​0.14), LOS (SMD -0.37, 95%CI -1.04, to 0.31, p ​= ​0.29), or odds of postoperative complications (OR 0.91, 95%CI 0.54, 1.55, p ​= ​0.73). All findings were supported by a very low quality body of evidence. Conclusions: Preoperative intervention was associated with better satisfaction and function in patients following THA when compared with no intervention or usual care. Preoperative intervention was found to have no effect on pain, and no effect on LOS or the odds of postoperative complications when compared with no intervention or usual care. All findings were supported by a body of evidence that was very low quality with unvalidated outcome measures and thus the true effect of the interventions is likely to be substantially different from the estimate of effect.PROSPERO Registration number: CRD42023429861.